ADVERTISEMENT EFFECTIVITY: VISIBILITY, CREDIBILITY, ATTRACTION AND POWER ON PURCHASING DECISION AND ITS IMPACT ON CUSTOMER SATISFACTION - Wulandari, Astri; Suryawardani, Bethani (Jurnal Aplikasi Manajemen, 2019)
Promotion is a one-way flow of information or persuasion created to direct a person or organization to actions that create exchanges in marketing. From four types of promotions, the most effective way to promote is through advertising. An effective advertisement is an advertisement that enables to communicate (has attraction to read, the attraction of attitude, easy to be remembered, be seen, be noticed, read the most) and to effect on selling to what has been advertised. This study was aimed to find out the influences of Visibility, Credibility, Attraction and Power on Purchasing Decision and its impact on Customer Satisfaction. The method of study implemented was quantitative explanatory research with data analysis technique of Structural Equation Modelling using SMART PLS software. The result of study showed that the contribution of Visibility (X1), Credibility (X2), Attraction (X3), and Power (X4) simultaneously influenced that directly influenced on Purchasing Decision (Y), that obtained 42.2%. The rest of 57.8% was influenced by other factors that are not included in this study. Meanwhile, the contribution of Visibility, Credibility, Attraction, Power and Purchasing Decision simultaneously influenced that directly influenced on Customer Satisfaction that obtained 73.27%. The rest of 26.73% was influenced by other factors that cannot be explained in this study. For further study, the next researcher can add more other variables to find out whether the influences of visibility, credibility, attraction, and power to purchasing decision and its impact is an effective way to as one of ways for company promotion.